Implications of Problem Based Learning Model on Students' Critical Thinking Ability in Arithmetic Sequence - Izzaroh, Iftitakhul; Prajitno, Sunyoto Hadi; Hadi, Susilo; Prayitno, Lydia Lia (Journal of Education and Learning Mathematics Research (JELMaR), 2025)
Effective education requires an approach that encourages ability to analyze critically, particularly when learning mathematics which is often considered challenging by students. Problem Based Learning model is considered capable of developing students' critical thinking abilities through real problem solving and collaboration. The purpose of this study is to find out how the Problem Based Learning approach affected the critical thinking abilities of Grade X students at SMAN 1 Driyorejo in the subject of arithmetic sequences throughout the 2024–2025 school year. The research employs an appropriate experimental design, namely the pretest-posttest control group design, and takes a quantitative approach.. The sample includes two classes: class X-6 as the experimental group implementing the Problem Based Leaning model, and class X-7 as the control group applying conventional teaching methods. Critical thinking assessments were used to gather data both before and after the intervention. To ascertain whether there was a significant difference between the two groups, the data were examined using a t-test. The findings indicated that the average pretest scores for the control and experimental classes were 31,91 and 58,71, respectively, while the average posttest scores were 46,48 and 90,05. Before testing the hypothesis, students' critical thinking test scores must be checked for normality and homogeneity to ensure the data is normally distributed and has the same variance. The data analysis's findings demonstrate the worth of t_count>t_table, result is |-19,826>-1,995 | for pretest questions and the value of t_count>t_table, result is |-48,278>-1,995| for posttest questions. Thus, when compared to conventional teaching approaches, the data analysis results demonstrate that the Problem Based Learning model significantly improves students' critical thinking abilities.Keyword: Problem Based Learning, Critical Thinking Abilities, Arithmetic Sequence